On Being a Scholar/Activist: An Introduction to Knowledge, Power, and Education - Michael W. Apple (Universidad Autónoma de Madrid, 2015)
This is an article for understanding a committed life story. Mike Apple makes a biographical narrative about how he became the scholar/activist who is. This story begins when he joined the Faculty of Education, as a student. He digs into his family roots and his original background and follows the path till today. He describes his experience in first person and provides a view from the inside about how different life experiences have been tacking to what Apple is as an educator and how he has built his work. He analyses his works, his readings, he describes his thoughts on power, education and curriculum. In his vital milestones, he notes that Wisconsin was a place where he could make a critical truly serious and committed work. A perfect place to become a "scholar/activist".